Pemaknaan Pesan Kesetaraan Gender dalam Iklan-iklan Femvertisingpada Penonton Laki-laki Etnis Betawi (Jurnal Ilmu Komunikasi dan Bisnis, 2023)
Gender equality is still a minority message in the Indonesian advertising industry which tends to be male centric. Femvertising as a form of correction to commodity feminism is still relatively new amid advertising audiences that are strongly influenced by patriarchal culture. In general, femvertising in Indonesia presents women as the main endorsers who carry messages of equality and empowerment. It is rare to find femvertising which displays men in the domestic area and does work that is identical to women's. GoPay, Arisan Mapan and Kecap ABC advertisements are three advertisements that dare to use the slice of life message approach by featuring male endorsers doing domestic work. Advertising messages that portray realities related to gender and roles in the domestic sphere can be interpreted in various ways by advertising audiences in a patriarchal society. One of the ethnic groups closely related to patriarchal culture is the Betawi ethnic group. This study aims to find out how the Betawi ethnic male audience interprets the message of gender equality in femvertising. The study used a constructivist paradigm with qualitative research and reception analysis methods from Stuart Hall. The results of the study involving five Betawi ethnic male informants aged early adulthood and married showed that there were three dominant positions and two negotiation positions. The most influential contextual factor in the meaning of messages is the socialization of family values. The Betawi ethnic factor, which is synonymous with patriarchal traditions, does not affect the acceptance of gender equality messages by informants.